Penyuluhan dan Pendampingan Guna Peningkatan Promosi Wisata Curup Kereta di Desa Rambang Jaya, Kecamatan Umpu Semenguk Kabupaten Way Kanan Propinsi Lampung - Arafat, Muhajir; Suryanto, Suryanto; Rusidi, Rusidi; As'ad, M; Faulina, Sri Tita; Arifin, Didik; Andriani, Nia; Hendrayudi, Hendrayudi; Agustina, Dian Sri; Kurniawan, Budi; Novari, Satria; Saputro, Haris (Universitas Pahlawan Tuanku Tambusai, 2024)
Curup Kereta is in the Rambang Jaya village area, Umpu Semenguk District, Way Kanan Regency, Lampung Province. Curup is a tourist destination with very promising potential because its beauty is stunning and beautiful. So it moved the lecturers at Mahakarya Asia University, Baturaja Campus, to help increase the promotion of the potential of train steeplechase tourism through cyberspace. This activity is carried out using direct counseling and assistance methods to create promotional content, both in the form of videos and images and directly uploading them on various social media platforms. With the increase in promotions through cyberspace, currently train cursing is becoming increasingly well known by the wider community. This is proven by the large number of people who see and watch the results of posts on social media from lecturers, students and the Rambang Jaya village community. So that the train curve is increasingly known to the wider community, not only local residents but also people outside the Way Kanan district, so that it can increase the number of tourists who visit the train curve. By increasing the number of tourists visiting, it can improve the economy of the RambangJaya village community.